In-vitro evaluation of the antifungal activities of eel skin mucus from Asian swamp eel (Monopterus albus) - Hilles, Ayah Rebhi; Mahmood, Syed; Kaderi, Mohd Arifin; Hashim, Ridzwan; Jalal, Tara K.; Salleh, Mueizzah Afkaarah (SciCell Publishing, 2019)
T Discovery and development of new drugs from marine and freshwater animal remain one of the most challenging areas in recent marine sciences field. Thus, the object of current study to examine the antifungal activity of Asian swamp eel (Monopterus albus) skin mucus. Eel skin mucus aqueous and methanol extracts were prepared with different extract concentrations from 0.49 to 1000 μg/mL against fungus pathogens i.e. Aspergillus niger and Microsporum gypseum. The antifungal assay conducted using well diffusion method. The results showed a dose dependent decrease the fungal growth, at 100µl/well, the inhibition zone of methanol extract against M. gypseum (25.7±0.75) mm, while the aqueous one was (23.3±0.16) mm Whereas eel skin mucus methanol and aqueous extracts showed lower inhibition zone against Aspergillus niger at the same concentration which was (11.1±0.59) mm and (9.0±0.15) mm respectively. The methanol extract showed the highest inhibitory activity against M. gypseum because M. gypseum infect the upper layers of the skin and eel skin mucus protect eels from infections. The results were statistically significant with p < 0.001. In conclusion, the present study carried out to reveal the antifungal activities of eel skin mucus which might be use as a source of antifungal agent.